Collagen IV differentially regulates planarian stem cell potency and lineage progression - Chan, Andy (Proc Natl Acad Sci U S A, 2021)
The extracellular matrix (ECM) provides a precise physical and molecular environment for cell maintenance, self-renewal, and differentiation in the stem cell niche. However, the nature and organization of the ECM niche is not well understood. The adult freshwater planarian Schmidtea mediterranea maintains a large population of multipotent stem cells (neoblasts), presenting an ideal model to study the role of the ECM niche in stem cell regulation. Here we tested the function of 165 planarian homologs of ECM and ECM-related genes in neoblast regulation. We identified the collagen gene family as one with differential effects in promoting or suppressing proliferation of neoblasts. col4-1, encoding a type IV collagen α-chain, had the strongest effect. RNA interference (RNAi) of col4-1 impaired tissue maintenance and regeneration, causing tissue regression. Finally, we provide evidence for an interaction between type IV collagen, the discoidin domain receptor, and neuregulin-7 (NRG-7), which constitutes a mechanism to regulate the balance of symmetric and asymmetric division of neoblasts via the NRG-7/EGFR pathway.